2019
DOI: 10.1007/s13201-019-0996-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of heavy metal background concentration in bottom sediment and risk assessment of sediment pollution by heavy metals in the Hrazdan River (Armenia)

Abstract: The purpose of this study is to determine background concentrations of heavy metals in bottom sediments, as well as to characterize potential danger of heavy metals in bottom sediments of the Hrazdan River. Linear regression method was used to determine background concentrations of metals in bottom sediments. While using this method, the linear regression of determining metal with a comparative element was used: The cobalt was chosen as a relative element, which is conditioned by the absence of significant sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…This observation is at variance with the findings of this study. However, the relatively higher metal levels in the sediments compared to the water samples are in consonance with values reported by earlier workers in the Hrazdan River (Armenia) and Lishui River, southern China watershed systems [36] [48].…”
Section: Discussionsupporting
confidence: 91%
“…This observation is at variance with the findings of this study. However, the relatively higher metal levels in the sediments compared to the water samples are in consonance with values reported by earlier workers in the Hrazdan River (Armenia) and Lishui River, southern China watershed systems [36] [48].…”
Section: Discussionsupporting
confidence: 91%
“…Instead, the subsurface layers (from 40 to 100 cm) exclusively represent the lithogenic contributions, since there is little probability of contamination through atmospheric deposition, and for this reason the subsurface horizon can be used to determine the local geochemical baseline [13]. In the hypothesis that it is not possible to carry out a subsurface soil horizon samples and the Regional Geochemical Baseline Mapping is not available, some studies [29][30][31] identify statistical methods (cumulative frequency and normalization method) as useful tools to define the geochemical baseline values. In order to assess the soil pollution status, some studies [28,[32][33][34][35][36] use some quantitative indexes: the geoaccumulation index (I geo ) and the enrichment factor (EF).…”
Section: Soil Pollution Status: the Definition Of Background Value (Bmentioning
confidence: 99%
“…In order to assess the soil pollution, it is necessary to define Geochemical Baseline Values in the study area. Some studies [29][30][31] have shown the need to use statistical methods to determine the geochemical baseline values. According to Zhou et al [29], the used statistical approach considers the combination between the cumulative frequency curve (CFD) and the normalization method through a linear regression.…”
Section: Geochemical Baseline Values Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The sedimentological approach is commonly used in ecological risk assessment of the aquatic environment [7][8][9]. However, one of its limitations is the absence of background concentrations due to lack of pristine (preindustrial) sediment environments devoid of anthropogenic contamination in most settings.…”
Section: Introductionmentioning
confidence: 99%